2020
DOI: 10.29333/pr/9295
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Views of the Implementation of STEM Approach in Secondary Schools and The Effects on Students

Abstract: STEM (Science, Technology, Engineering and Mathematics) approach is considered important by many countries and projects carried out in order to integrate into their curriculum. The widespread use of STEM is only possible if teachers have positive thoughts, knowledge and experiences about it. In this study, it is aimed to answer these research questions: "What do teachers think about the gains their students will achieve if STEM activities are implemented to their students?" and "What do they think about the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Ruiz-Mallén et al ( 2017) also agreed that the involvement in the artistic experience enables the retain more females in science learning. Hence, the STEAM integrated approach enables the transformation of the theoretical knowledge into practice and creating an environment for the design and product development as agreed by Tunc and Bagceci (2021), as well as nurture the problem-solving skills in order to prepare students in placing the thinking and exploration in daily life (Gunawan & Shieh, 2020). Students' experience in the calculation (Mathematics) is also being enhanced when students learn about the electric current in the circuit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruiz-Mallén et al ( 2017) also agreed that the involvement in the artistic experience enables the retain more females in science learning. Hence, the STEAM integrated approach enables the transformation of the theoretical knowledge into practice and creating an environment for the design and product development as agreed by Tunc and Bagceci (2021), as well as nurture the problem-solving skills in order to prepare students in placing the thinking and exploration in daily life (Gunawan & Shieh, 2020). Students' experience in the calculation (Mathematics) is also being enhanced when students learn about the electric current in the circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Both STEM and STEAM education encompasses the disciplines of science, technology, engineering, and mathematics in an integrated manner (Tunc & Bagceci, 2021) while educating students to design solutions in solving real-world problems. In comparison, STEM and STEAM education might overlap on specific methodology; however, STEAM introduces the concept of artistic discipline (Kang, 2019), fostering creativity, global awareness, design, and literature (Baek et al, 2012).…”
Section: It Is Steam and Not Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…The place of integrated STEM education in chemistry is naturally ordained as chemistry subject itself is central to science, mingled with mathematics from inception and modern with the copulation of technology and engineering. Students ought to experience this integration to improve learning outcomes and become better chemists (Tunc & Bagceci, 2021). The educational stakeholders saddled with the responsibility of making the integration work out as expected in turn to retain students in STEM disciplines are the in service teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Al Salami et al (2017) described PDP as a complex process in which teachers must be cognitively and emotionally involved and enumerated different factors (structure of PD, context, and teacher characteristics) required for a successful PDP. Recently, science educators and researchers emphasize the importance of PDP for in service STEM teachers and investigated the effect of PD on students learning outcomes (Chirume, 2017;Du et al, 2019;Fletcher-Wood & Zuccollo, 2020;Tunc & Bagceci, 2021). In particular, Barlow et al (2014) reported that teachers that consistently attend PD are more effective than teachers who do not which in turn result to higher grade for students of the PD teachers.…”
Section: Introductionmentioning
confidence: 99%